2003
DOI: 10.1212/01.wnl.0000081306.86961.33
|View full text |Cite
|
Sign up to set email alerts
|

Productive infection of cerebellar granule cell neurons by JC virus in an HIV+ individual

Abstract: JCV can productively infect granule cell neurons of the IGCL of the cerebellum. This suggests a role for JCV infection of neurons in cerebellar atrophy occurring in HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 23 publications
2
91
1
1
Order By: Relevance
“…Other JCPyV-associated central nervous system disorders -JCPyV-mediated granule cell neuronopathy describes the cytopathic replication of JCPyV in granule cell neurons of the cerebellum (227,228). Clinically, this entity is characterized by a cerebellar syndrome with ataxia and progressive cerebellar atrophy.…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…Other JCPyV-associated central nervous system disorders -JCPyV-mediated granule cell neuronopathy describes the cytopathic replication of JCPyV in granule cell neurons of the cerebellum (227,228). Clinically, this entity is characterized by a cerebellar syndrome with ataxia and progressive cerebellar atrophy.…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…He had no history of alcohol intake. Since the initiation of highly active antiretroviral therapy (HAART) (lopinavir, ritonavir, emtricitabine, and tenofovir) in 2007, plasma HIV RNA had remained undetectable for 8 months but his absolute CD4 ϩ lymphocyte count always remained below 50/mm 3 and he had uncontrolled mycobacterial intra-abdominal infection.…”
Section: Case Reportmentioning
confidence: 99%
“…In a few cases, PML has also been associated with alterations in the gray matter. JCV has recently been involved in a neuronal infection restricted to the granule layer of the cerebellum (3,9,11) and is now considered the etiology of a new entity named JC virus granule cell neuronopathy (GCN). The factors involved in the development of JCV-associated neuronal disorders are poorly understood.…”
mentioning
confidence: 99%
“…We have previously characterized two HLA-A*0201-restricted epitopes of JCV major capsid protein VP1 recognized by CD8 ϩ cytotoxic T lymphocytes (CTL) and studied the role of these cells in PML patients and control subjects (12,23). The presence of JCV-specific CTL was associated with a favorable outcome of PML (13), and these cells could be detected in the blood of 73% of healthy individuals (14), suggesting that the cellular immune response against the JCV VP1 protein may be important in the containment of JCV and the prevention of PML (10,11,13,21,23,24).We therefore hypothesized that the BKV VP1 protein may play a similar role. Indeed, in parallel to our studies on the cellular immune response to BKV (5), Krymskaya et al (26) also recently independently reported that the BKV VP1-specific epitope p108 (VP1 p108 ) cross-reacted with JCV VP1 p100 in healthy subjects and in two KTx recipients.…”
mentioning
confidence: 99%